Using a Cournot-Nash model to study the contributions of cooperation for fishing stocks recover and for fishers' rents - Filipe, J. A. C. B. (2007)
In our study we implement a model to explain the recover of stocks of a common resource pool in the fisheries area. Our aim is to model the behavior of two Fishing Companies through a model supported in Cournot model and in Nash principles of equilibrium. Our Cournot-Nash model is supported in the competing behavior of agents. Afterwards, we present an adjusted model to study the results of cooperation between agents. We can see that cooperation brings up procedures that allow conservation of species and stocks recover. We conclude that agents' cooperation brings the possibility to get good results for species preservation and good rents for fishers.